La incorporación de la inteligencia artificial generativa en las prácticas de investigación y escritura de científicos mexicanos - Santiago-Ruiz, Eduardo (2024)
This article examines the incorporation of artificial intelligence (AI) in the research and writing practices of Mexican scientists. Semi-structured interviews were conducted with researchers in the fields of biology, biological sciences, and biomedical sciences. The most common use of AI tools was found to be to improve, transform, and adapt texts, especially in correcting English manuscripts, thus facilitating publication in international contexts. Other uses include searches in the literature, support as a virtual tutor, preliminary data interpretation, and generation of programming code for statistical analysis. Only one participant uses AI as a research assistant to define objectives and methodologies. All participants agreed that AI improves their efficiency. However, they also identified significant problems, such as plagiarism, information leakage, and academic dishonesty. Several reported the misuse of complete AI-generated texts, a practice observed in both students and established researchers. Taking into account these challenges, it is essential to implement training programs, awareness campaigns, and establish updated ethical guidelines. The article concludes with recommendations to improve transparency and declaration of AI use in research.